Metagenomic Analysis of the Diversity of DNA Viruses in the Surface and Deep Sea of the South China Sea - Liang, Yantao; Wang, Long; Wang, Zengmeng; Zhao, Jiulong; Yang, Qingwei; Wang, Min; Yang, Kaiguang; Zhang, Lihua; Jiao, Nianzhi; Zhang, Yongyu (Frontiers in Microbiology, 2019)
A metagenomic analysis of the viral community from five surface and five deep sea water (>2000 m below the surface, mbs) samples collected from the central basin of the South China Sea and adjacent Northwest Pacific Ocean during July–August 2017 was conducted herein. We builded up a South China Sea DNA virome (SCSV) dataset of 29,967 viral Operational Taxonomic Units (vOTUs), which is comparable to the viral populations from the original Tara Ocean and Malaspina expeditions. The most abundant and widespread viral populations were from the uncultivated viruses annotated from the viral metagenomics. Only 74 and 37 vOTUs have similarity with the reported genomes from the cultivated viruses and the single-virus genomics, respectively. The community structures of deep sea viromes in the SCSV were generally different from the surface viromes. The carbon flux and nutrients (PO4 and NOx) were related to the surface and deep sea viromes in the SCSV, respectively. In the SCSV, the annotated vOTUs could be affiliated to the cultivated viruses mainly including Pelagibacter (SAR11) phage HTVC010P, Prochlorococcus phages (P-GSP1, P-SSM4, and P-TIM68), Cyanophages (MED4-184 and MED4-117) and Mycobacterium phages (Sparky and Squirty). It indicated that phage infection to the SAR11 cluster may occur ubiquitously and has significant impacts on bathypelagic SAR11 communities in the deep sea. Meanwhile, as Prochlorococcus is prominently distributed in the euphotic ocean, the existence of their potential phages in the deep sea suggested the sedimentation mechanism might contribute to the formation of the deep sea viromes. Intriguingly, the presence of Mycobacterium phages only in the deep sea viromes, suggests inhabitance of endemic viral populations in the deep sea viromes in the SCSV. This study provided an insight of the viral community in the South China Sea and for the first time uncovered the deep sea viral diversity in the central basin of the South China Sea.